2019
DOI: 10.1029/2019je006133
|View full text |Cite
|
Sign up to set email alerts
|

Chlorate as a Potential Oxidant on Mars: Rates and Products of Dissolved Fe(II) Oxidation

Abstract: Oxychlorine species are globally widespread across the Martian surface. Despite their ubiquitous presence, the ability of oxychlorine species to serve as oxidants on Mars has largely been unexplored. While perchlorate is kinetically inert, chlorate may be a critical Fe(II) oxidant on Mars. However, the timescale over which chlorate may oxidize Fe(II) and the mineral products formed in Mars‐relevant fluids are unclear. Fe(II) oxidation by chlorate was thus investigated in magnesium chloride, sulfate, and perchl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(82 citation statements)
references
References 168 publications
12
70
0
Order By: Relevance
“…If the soils near early Jezero lakes contained detrital Mg carbonates provided from the Nili Fossae region, local groundwater seepage would have also provided an abundance of dissolved Mg and alkalinity to the lakes, which in turn could have caused authigenic precipitation of lacustrine carbonates [43]. Our results also support the idea that shallow pools in wetlands in semi−arid climates of early Mars would have transported salinity and oxidizing materials to the subsurface groundwater through infiltration [8,44]. We suggest that closed−basin lakes in semi−arid climates on early Mars would have been sustained by multiple types of groundwater inflows (e.g., local seepage, regional flows, and upwelling of deep groundwater [11]), which would have generated redox disequilibria in the lacustrine environments and could have affected the past habitability.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…If the soils near early Jezero lakes contained detrital Mg carbonates provided from the Nili Fossae region, local groundwater seepage would have also provided an abundance of dissolved Mg and alkalinity to the lakes, which in turn could have caused authigenic precipitation of lacustrine carbonates [43]. Our results also support the idea that shallow pools in wetlands in semi−arid climates of early Mars would have transported salinity and oxidizing materials to the subsurface groundwater through infiltration [8,44]. We suggest that closed−basin lakes in semi−arid climates on early Mars would have been sustained by multiple types of groundwater inflows (e.g., local seepage, regional flows, and upwelling of deep groundwater [11]), which would have generated redox disequilibria in the lacustrine environments and could have affected the past habitability.…”
Section: Discussionsupporting
confidence: 76%
“…Irradiation from solar UV light would have also oxidized and acidified surface water through photo−oxidation of ferrous ions [45]. If oxidizing surface water infiltrated the wetlands of semi−arid climates on early Mars, highly reactive oxychlorides (e.g., ClO 3 − ) would have oxidized the subsurface materials, as suggested previously [44,46]. Less reactive Cl − , Na + , and ClO 4 − in infiltrating surface water could have been transported into deep lakes through regional groundwater flows, as proposed by [8].…”
Section: Implications For Hydrogeochemical Cycles Around Lakes On Earmentioning
confidence: 72%
“…This scenario implies the addition of oxidant species into the fluids. Although the source of oxidant remains largely unconstrained, we propose chlorates as a possible candidate for Fe 2+ oxidation due to its occurrence in red Jura (McAdam et al, 2020), and the detection of akaganeite minerals expected from such reaction (Mitra & Catalano, 2019), observed in both Pettegrove Point and red Jura.…”
Section: Discussionmentioning
confidence: 91%
“…Oxychlorine species were recorded in the red Jura (McAdam et al, 2020) and were not observed since the Buckskin drill sample at the Marias Pass, lower in the Mount Sharp sequence (~250 m of stratigraphy below VRR). Actually, chlorate and sulfate in solution with dissolved Fe 2+ would produce goethite and/or lepidocrocite as well as akaganeite and jarosite (both observed in Jura member) in a wide range of pH (Mitra & Catalano, 2019). The possible preservation of apatite minerals in the red Jura (Forni et al, 2019; Rampe et al, 2020), which are unstable in acidic media, probably implies that the fluid flow event was not long‐lived and/or was highly localized in its effect.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, formation of this gray hematite by ripening of red hematite at lower temperatures (Langmuir, 1971; Wang et al, 2015) over long periods of aqueous interaction could have occurred. Also, Wong et al (2020) hypothesize that interaction between sulfite‐bearing groundwater (Halevy et al, 2007; Halevy & Schrag, 2009) and hematite could have resulted in precipitation of magnetite that was later reoxidized by materials such as oxychlorine phases (Brundrett et al, 2019; Mitra & Catalano, 2019) and nitrate/nitrite (e.g., Dhakal et al, 2013) in fluids similar to those that precipitated oxychlorine and nitrate/nitrite salts at Rock Hall. This process does not require warm fluids, and the hematite formed would be martite, a pseudomorph of magnetite that is indistinguishable from gray hematite in XRD analysis.…”
Section: Discussionmentioning
confidence: 99%